2013
DOI: 10.5194/acp-13-3979-2013
|View full text |Cite
|
Sign up to set email alerts
|

The physical and chemical characteristics of marine primary organic aerosol: a review

Abstract: Knowledge of the physical characteristics and chemical composition of marine organic aerosols is needed for the quantification of their effects on solar radiation transfer and cloud processes. This review examines research pertinent to the chemical composition, size distribution, mixing state, emission mechanism, photochemical oxidation and climatic impact of marine primary organic aerosol (POA) associated with sea-spray. Numerous measurements have shown that both the ambient mass concentration of marine POA a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
261
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(275 citation statements)
references
References 161 publications
12
261
1
1
Order By: Relevance
“…Novakov et al (1997) collected aerosol particles < 600 nm in the marine trade wind region on Puerto Rico and found that they contained a fraction of soluble organic material which exceeded that of sulfates. Generally, the ocean has been assumed to be a source of organic particulate matter, a topic on which a review can be found in Gantt and Meskhidze (2013). It has therefore been speculated that the organic fraction of marine aerosol has an influence on number concentrations of particles and CCN and on their hygroscopicity.…”
mentioning
confidence: 99%
“…Novakov et al (1997) collected aerosol particles < 600 nm in the marine trade wind region on Puerto Rico and found that they contained a fraction of soluble organic material which exceeded that of sulfates. Generally, the ocean has been assumed to be a source of organic particulate matter, a topic on which a review can be found in Gantt and Meskhidze (2013). It has therefore been speculated that the organic fraction of marine aerosol has an influence on number concentrations of particles and CCN and on their hygroscopicity.…”
mentioning
confidence: 99%
“…Rising bubbles scavenge surface active organic material from the water column at their interfaces and this process facilitates the formation of the organic enriched sea-air interface known as the sea surface microlayer (SML). This organic material is ejected into the atmosphere during bubble bursting resulting in sea spray aerosol containing similar organic material to that of the microlayer [12][13][14][15][16][17][18][19] ( Figure 1). Measurements of atmospheric INP concentrations in the remote oceans indicate that there may be a marine source of INPs linked to marine biology [3][4][5] , and modelling work indicates that this may be important in mixed phase clouds 9,10 .…”
mentioning
confidence: 99%
“…Organic material makes up a substantial fraction of sub-micron sea-spray aerosol and it is estimated that 10±5 Tg yr -1 of primary organic sub-micron aerosol is emitted from marine sources globally 12 . Rising bubbles scavenge surface active organic material from the water column at their interfaces and this process facilitates the formation of the organic enriched sea-air interface known as the sea surface microlayer (SML).…”
mentioning
confidence: 99%
See 2 more Smart Citations